Modeniti & hubungannya dengan idea kemajuan - Nasruddin Yunos; Siti Nor Baya Mat Yacob (Universiti Kebangsaan Malaysia, 2007)
Rooted from the Greece and Roman scholastic discourses, the idea of progress became a dominant worldview, especially after the Renaissance. Darwin's theory of evolution is the symbol of maturity of the idea of progress. On the positive side, the evolution theory not only influenced on the scientific development but the humanities as well. After the Renaissance, the idea of progress becomes more relevant as the idea of modernity took place. Later on, the root for the idea of progress became the main idea for modernity. Modernity, with its own characteristic, is the material basis for modernization and modernism is the ideological framework of modernization